2019
DOI: 10.1039/c9cc02418b
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of 1,3,5,7-cyclooctatetraene by a molecular calcium hydride: an even electron polarised insertion/deprotonation mechanism

Abstract: The reductive aromatisation of 1,3,5,7-cyclooctatetraene by a dimeric calcium hydride occurs via two electron steps and does not necessitate the formation of radical intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
(49 reference statements)
1
21
0
2
Order By: Relevance
“…The Yb1‐COT cent distance (2.0080(3) Å) and Yb1‐COT cent ‐Yb1a (180.0(6)°) angle is consistent with previously isolated ytterbium(II) inverse sandwich complexes bearing the [COT] 2− dianion (1.909–2.109 Å and 178.9–179.5° respectively) [33–35] . Additionally, compound 2 is also isostructural with the recently isolated dicalcium analogue [36] . The coordination sphere of the ytterbium center is completed by two Yb−N bonds (2.3890(19) and 2.4027(18) Å) from the β‐ diketiminato ligand.…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The Yb1‐COT cent distance (2.0080(3) Å) and Yb1‐COT cent ‐Yb1a (180.0(6)°) angle is consistent with previously isolated ytterbium(II) inverse sandwich complexes bearing the [COT] 2− dianion (1.909–2.109 Å and 178.9–179.5° respectively) [33–35] . Additionally, compound 2 is also isostructural with the recently isolated dicalcium analogue [36] . The coordination sphere of the ytterbium center is completed by two Yb−N bonds (2.3890(19) and 2.4027(18) Å) from the β‐ diketiminato ligand.…”
Section: Methodssupporting
confidence: 85%
“…[33][34][35] Additionally, compound 2 is also isostructural with the recently isolated dicalcium analogue. [36] The coordination sphere of the ytterbium center is completed by two YbÀ N bonds (2.3890( 19) and 2.4027(18) Å) from the β-diketiminato ligand. Three bimetallic ytterbium(II) complexes bearing a μ-[COT] 2À dianion have been structurally authenticated, however, all have been synthesised by either; salt metathesis reaction between K 2 C 8 H 8 and a ytterbium halide [34] or a metaethical reaction between Cp* 2 Yb and COT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…28-30 kcal mol À1 )a ssociated with this attack varies with the position of hydride addition and may be compared to the analogous process computed for COT (21.8 kcal mol À1 ). [7] Following the intrinsic reaction coordinate in all cases leads to the formation of dicalcium tetracenyl intermediates (Cf/Ch/Cg)t hat retain aC a-m 2 -H-Ca linkage similar to that identified during the reaction with benzene. While there is little to discriminate the kinetic facility of the nucleophilic attack, the formation of intermediates Cf-h is endothermic due to the disruption of the tetracene p system and their relative stabilities depend on the position of hydride addition (Cf,16.1; Cg 13.7; Ch 6.2 kcal mol À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[3] Computational analysis using density functional theory (DFT) indicated reactions of 2 with C=Cm ultiple bonds are highly polarized and proceed in as tepwise fashion with no necessary rupture of either the dinuclear hydride or the dinuclear hydrido-alkyl intermediates formed during the reactions.The dimeric structure of 2 is particularly significant during its reaction with 1,3,5,7-cyclooctatetraene (COT)t o yield the inverse sandwich dicalcium cyclooctatetraenyl [COT] 2À derivative (4,S cheme 1). [7] Although the two electron reduction of COT is typically achieved by its stepwise reaction with as uitable alkali metal, [8] monitoring of the formation of 4 by EPR spectroscopy did not provide any evidence of single electron transfer or radicaloid intermediates.R ather,D FT analysis indicated that reduction proceeds via ap athway involving consecutive polarized Ca À H/C = C insertion and intramolecular deprotonation, which is imposed by the retention of dicalcium species throughout the reaction.…”
mentioning
confidence: 99%